Psychological predictors of sport injuries among junior soccer players - Johnson, J.; Ivarsson, A. (Scandinavian Journal of Medicine & Science in Sports, 2011)
Previous researches have established models that specify psychological factors that could predict sport injuries. One example is Williams and Andersen's stress-injury model stressing factors such as anxiety, negative life stress and few coping resources. The purpose of the current study was to find psychological factors that could lead to an increased injury risk among junior soccer players, in addition to construct an empirical model of injury risk factors for soccer players. The participants were 108 male and female soccer players (m=17, 6) studying at soccer high schools in southwest Sweden. Five questionnaires were used, State Trait Anxiety Inventory, Sport Anxiety Scale, Life Events Survey for Collegiate Athletes, Athletic Coping Skills Inventory-28 and Swedish universities Scales of Personality. Injury record was collected by athletic trainers at the schools during a period of 8 months. The result suggested four significant predictors that together could explain 23% of injury occurrence. The main factors are life event stress, somatic trait anxiety, mistrust and ineffective coping. These findings partly support Williams and Andersen's stress-injury model and are organized into an empirical model. Recommendations are given to sport medicine teams and coaches concerning issues in sport injury prevention.